Financial constraints and the growth and survival of innovative start‐ups: An analysis of Italian firms. (10th July 2020) - Ferrucci, Edoardo; Guida, Roberto; Meliciani, Valentina
Abstract: We study the impact of measures devoted to relieving financial constraints for the growth and survival of Italian innovative start‐ups. Using balance sheet data on innovative start‐ups and information on the use of the Italian Central Guarantee Fund for small and medium‐sized enterprises, we evaluate whether access to the fund, relieving financial constraints, helps innovative start‐ups survive and grow. We find innovative start‐ups benefit significantly more than similar control firms. We shed light on the relevance of policies aimed at reducing financial constraints for the growth and survival of innovative start‐ups, an issue receiving increasing attention at the European level.